2015
DOI: 10.1212/wnl.0000000000001991
|View full text |Cite
|
Sign up to set email alerts
|

Detailed comparison of amyloid PET and CSF biomarkers for identifying early Alzheimer disease

Abstract: Objective:To compare the diagnostic accuracy of CSF biomarkers and amyloid PET for diagnosing early-stage Alzheimer disease (AD).Methods:From the prospective, longitudinal BioFINDER study, we included 122 healthy elderly and 34 patients with mild cognitive impairment who developed AD dementia within 3 years (MCI-AD). β-Amyloid (Aβ) deposition in 9 brain regions was examined with [18F]-flutemetamol PET. CSF was analyzed with INNOTEST and EUROIMMUN ELISAs. The results were replicated in 146 controls and 64 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
213
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 307 publications
(228 citation statements)
references
References 40 publications
14
213
1
Order By: Relevance
“…In that study, increased amyloid deposition by PET, but not CSF Aβ42, significantly correlated with disease stage among patients with mild cognitive symptoms. The same authors recently reported that the diagnostic accuracy of CSF biomarkers and amyloid PET for diagnosing early-stage AD is comparable [34]. A previously published report, with similar design to the present study, failed to demonstrate an association between CSF biomarkers and cognitive decline in non-demented elderly [31].…”
Section: Discussionsupporting
confidence: 64%
“…In that study, increased amyloid deposition by PET, but not CSF Aβ42, significantly correlated with disease stage among patients with mild cognitive symptoms. The same authors recently reported that the diagnostic accuracy of CSF biomarkers and amyloid PET for diagnosing early-stage AD is comparable [34]. A previously published report, with similar design to the present study, failed to demonstrate an association between CSF biomarkers and cognitive decline in non-demented elderly [31].…”
Section: Discussionsupporting
confidence: 64%
“…In early-onset FAD, Aβ42 levels were reduced already 25 years before cognitive symptoms [403]. The inverse correlation between Aβ42 in the cerebrospinal fluid and extracellular insoluble plaque deposits from PET imaging [404] strongly indicates that the soluble pools of Aβ42 have been depleted in favor of the deposits; since the deposits are not pathogenic, depletion of soluble Aβ42 seems consistent with loss of soluble Aβ from the neurons, i.e. if the overall soluble pool of functional Aβ has been depleted in favor of non.functional oligomers and aggregates.…”
Section: Loss Of Function Is Consistent With Aβ-related Biomarkers Ofmentioning
confidence: 94%
“…CSF levels of Aβ42 and Aβ40 were analyzed with Euroimmun immunoassay (EUROIMMUN AG, Lübeck, Germany)2324 in all study participants. This was done before the analysis of plasma samples using Simoa platform.…”
Section: Methodsmentioning
confidence: 99%